Bell pepper germination and seedling’s parameters under different osmotic potentials - Forigo Beloti, Igor; Alves de Sousa, Luciana; Oliveira, Roberta Camargos; Miranda Lemes, Ernane (Comunicata Scientiae, 2022)
Bell pepper (Capsicum annuum L.) is the third most cultivated Solanaceae species in Brazil and is highly sensitive to osmotic stresses. The increasing soil salinity is a frequent problem that hinders the plant absorption of water and nutrients by the roots, limiting agricultural production. Therefore, this study’s objectives were to evaluate the germination, vigor, and development of bell pepper commercial cultivars after NaCl treatments to simulate osmotic stress. Five cultivars (Yolo wonder, SF134 yellow, Marta, All big red, Cascadura) were submitted to four osmotic potentials (salt stresses of 0, -0.3, -0.6, -0.9 MPa) in a factorial scheme of 5×4, with four repetitions. The results indicated that the bell pepper germination is highly affected according to the presence of NaCl. The bell pepper germination supports NaCl concentrations equal to or higher than -0.3 MPa osmotic potential. Significant reductions in germination, germination speed index, seedling length, and dry mass as the salinity increases - osmotic potential decrease. The yellow bell pepper ‘SF134’ presented similar germination down to -0.6 MPa and can be cultivated in regions with salinity problems. The green bell pepper ‘Cascadura’ presented great germination, germination speed index and dry mass, and superior seedling length, being indicated for cultivation in more diverse environments.